THE IN/TRAINING OF THE SCHOOL MANAGER TO DEAL WITH SEXUALITY - Castro Leao, Andreza Marques de [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2018)
The present study aimed to know the difficulties and facilities of managers in dealing with situations involving sexuality in school. In addition, it sought to investigate subjects that they consider relevant to be worked on in a course directed to train education professionals. The purpose of these findings was to outline a continuing training course aimed at preparing them for sex education work, given the need to instrumentalize them. A total of 40 school managers from a municipality located in the interior of the state of Sao Paulo participated in the qualitative-quantitative research. Their participation consisted in responding to a semi-closed questionnaire with questions related to sexuality and sex education. Their notes point to the need for training in different subjects of sexuality, especially in child sexuality, sexual diversity, sexual violence, sexuality and disabilities, myths, taboos and sexual prejudices, among others. They report that they find it difficult to answer the students' questions and it is more difficult to work on issues involving sexual diversity, masturbation, teenage pregnancy and finding out about sexual violence. There were few notes about the 'facilities' to cover this topic. In summary, these data highlight their formative need and provided important elements for the elaboration of a continuing education course to prepare them for the implementation of sex education projects. This course focused on the theoretical basis of these participants, a strategy of sensitizing them, by proposing the reading of scientific texts focused on the themes of sexuality and sex education.
Keywords: Continuing teacher training; School manager; Sexuality; Sexual Education